2018
DOI: 10.1111/evj.12953
|View full text |Cite
|
Sign up to set email alerts
|

Noncatastrophic and catastrophic fractures in racing Thoroughbreds at the Hong Kong Jockey Club

Abstract: There were 3.6 times as many noncatastrophic fractures as catastrophic fractures in Thoroughbreds racing in Hong Kong between 2004 and 2011. Noncatastrophic fractures interfere with race training schedules and may predispose to catastrophic fracture. Future analytical studies on noncatastrophic racing fractures should be a priority for the racing industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…However, caution should be exercised when interpreting these findings. The significant heterogeneity indicates that we are not comparing equivalent studies, and the variability between studies is too high [ 63 ]. This high variability is preventing a reliable assessment of the effect of these measures of HSEH on MSI.…”
Section: Discussionmentioning
confidence: 99%
“…However, caution should be exercised when interpreting these findings. The significant heterogeneity indicates that we are not comparing equivalent studies, and the variability between studies is too high [ 63 ]. This high variability is preventing a reliable assessment of the effect of these measures of HSEH on MSI.…”
Section: Discussionmentioning
confidence: 99%
“…Fatal MSI were evenly distributed between two-year-old (6/12, 50%) and older horses (6/12, 50%) in this study. Other studies have also found that the occurrence of fatal MSI was not affected by age [5,17,34].…”
Section: Discussionmentioning
confidence: 89%
“…However, this was not significant for injuries overall [33]. Other studies report age did not affect the incidence of MSI [5,17,34]. The inconsistent association between age and MSI may be due to variation in case definitions, study populations, and geographical locations, or a combination of these factors.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…), and in Hong Kong (Sun et al . ). While this study has only been conducted on a limited number of horses, results indicate that racing horses with symptoms of TJS carries a low risk of catastrophic breakdown in the fetlock during racing.…”
Section: Discussionmentioning
confidence: 97%